Wildlife Farms, Stigma and Harm - Jessica Bell Rizzolo (Animals, 2020)
Wildlife farming, the commercial breeding and legal sale of non-domesticated species, is an increasingly prevalent, persistently controversial, and understudied conservation practice. The adoption or rejection of wildlife farms is a complex process that incorporates numerous ethical considerations: conservation, livelihoods, animal welfare, and cultural practices. This paper uses qualitative interview data with key informants (academics) to analyze (a) the harms and benefits of wildlife farms and (b) the factors that influence whether wildlife farms are stigmatized or accepted. In evaluations of wildlife farming’s harms and benefits, respondents incorporated multiple considerations: animal welfare, environmental impacts, scale disparities between sustenance and commercial farms, consumer preferences, species differences, the substitutability and accessibility of wildlife products, and governance. The results further indicated that the stigmatization or acceptance of wildlife farms is affected by the “wildlife farm” label, if there is a stigma around use of a species, a form of production, or the perceived quality of a wildlife product, cultural differences in wildlife use, wildlife consumer typology, geopolitical factors, and demand reduction efforts. This paper analyzes the complexities of wildlife farming such that stakeholders can understand the impacts of this practice on species, human communities, individual animals, and the legal and illegal wildlife trades.